Role of Victims in Criminal Action of Rape Against Children in Pemalang State Court - R. Ayu Miya Ratih Ardhya Garini; Sri Kusriyah (Law Development Journal, 2021)
This study aims to analyze the role of the victim considered by the judge in deciding criminal cases of rape against children and the role of victims against children influences the imposition of criminal sanctions by judges at the Pemalang District Court. This research was conducted using a sociological juridical approach with the research specifications used in this research is descriptive in nature equipped with a case study of aspects of the role of the victim in considering the severity of the punishment given to the perpetrator of rape against children in Pemalang District Court, that children also have role in the occurrence of the crime of rape, whether the victim is active, passive, provocative, consciously or unconsciously. Based on the results of the research, it was concluded that the Pemalang District Court Judge had considered the aspects of the role of the victim in the criminal case of rape against children, that the role of the victim in the crime of rape against children was something that mitigated the crime imposed on the perpetrator.